Community-acquired bacteraemia in COVID-19 in comparison to influenza A and influenza B: a retrospective cohort study - Thelen, JM; Buenen, AGN; van Apeldoorn, M; Wertheim, HF; Hermans, MHA; Wever, PC (BioMed Central, 2021)
Background During the coronavirus disease 2019 (COVID-19) pandemic in the Netherlands it was noticed that very few blood cultures from COVID-19 patients turned positive with clinically relevant bacteria. This was particularly evident in comparison to the number of positive blood cultures during previous seasonal epidemics of influenza. This observation raised questions about the occurrence and causative microorganisms of bacteraemia in COVID-19 patients, especially in the perspective of the widely reported overuse of antibiotics and the rising rate of antibiotic resistance.